Capital Management Strategy in Down Trending Market for Profit Maximization - Sutradhar, Sumit (Indian Journal of Research in Capital Markets, 2021)
The majority of short-term investors and long-term investors go for following the trend based on fundamental analysis more than technical analysis. In India, many retail investors lose a huge amount of money due to insufficient strategy and lack of knowledge about investments. While buying a stock, the investor has decided the final selling price and duration of investment and the investor simply trades on the daily candle or closing price of the market. This paper provided an efficient strategy for managing the adversities of the market, that is, following the downtrend though the investor is overall bullish for a stock, exiting the trade at breakeven point or when the end of downtrend is confirmed before or after the breakeven point. At this point of market reversal, which is now lower than the previous buying price, entering the market with the remaining capital after profit and loss and with same or little higher return goal, the expected returns on investments can be redeemed at a faster rate. The price at which investment goals can be achieved is given by the healing index.